Environmental Literacy and Green Accounting in MSMEs - Dunakhir, Samirah; Hanisyahputra, Farhan Dwinanda; Dahlan, Lukman; Zaimar , Fina Ruzika (Journal of Social Science and Business Studies, 2025)
This study aims to analyze the relationship between environmental literacy and the application of green accounting principles in Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative approach and survey method, 400 MSME owners/managers were selected. Purposive sampling was used to select businesses that had been operating for at least three years and had a prior awareness of environmental issues. Data analysis was performed using linear regression and correlation tests using SPSS 25 software. The results indicate that environmental literacy has a positive and significant effect on the implementation of green accounting. This finding confirms that environmental literacy is a strategic, knowledge-based resource consistent with the Resource-Based View (RBV) perspective, thus providing a competitive advantage for MSMEs in the transition to a green economy. This study provides theoretical contributions by expanding the application of RBV to sustainability accounting, as well as practical contributions for MSMEs and policymakers in designing environmental literacy improvement programs to accelerate the adoption of green accounting.